The study of consumer awareness towards Agromas product / Siti Roodeeyah Md Isa - Md Isa, Siti Roodeeyah (Faculty of Business and Management, 2004)
Agromas is a processed product produced by Federal Agriculture Marketing Authority (FAMA). This product has been in the market for such a long time but the level of consumer awareness towards these products is quite low. Majority of consumer are not aware of the product variety under Agromas brand name. This low awareness among consumer towards Agromas products can affect the survival of these products in the future. Due to this unawareness problem, this study is done to identify the level of awareness among consumer in Alor Gajah District towards Agromas product. This study also does examine the weaknesses of FAMA in marketing its Agromas products and provide recommendation in improving Agromas marketing strategies. Beside questionnaires and interview, other methods of research that have been applied in this study are data collection, simple random sampling technique and analyze data using Statistical Package for Social Sciences (SPSS). Hopefully the findings of this study can aid FAMA in marketing Agromas products successfully.